Pengaruh Customer Relationship Management terhadap Peningkatan Jumlah Mahasiswa Universitas Dharmawangsa - Khaira Rizfia Fahrudin (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to determine the extent to which people (human resources) and technology influence the increase in student enrollment at Dharmawangsa University. The research employs a quantitative method, in which data are expressed in numerical form and analyzed using statistical techniques. Data were collected through both library research and field research conducted systematically in accordance with the research objectives. The analytical methods used to address the research problems and test the hypotheses include descriptive analysis and regression analysis. The results of the t-test indicate that the people (human resources) variable has a positive and significant effect on the increase in student enrollment at Dharmawangsa University, where the calculated t-value (t = 2.05183) exceeds the critical t-value, indicating that H? is accepted and that there is a significant relationship between human resources and the increase in student enrollment. Similarly, the technology variable has a positive and significant effect on the increase in student enrollment, with the calculated t-value (t = 2.05183) exceeding the critical t-value (t = 2.071), indicating that H? is accepted and that technology is significantly associated with the increase in student enrollment. Furthermore, the F-test results show that the calculated F-value (127.161) is greater than the critical F-value (3.35), indicating that the independent variables—people (human resources) and technology—simultaneously have a significant effect on the dependent variable, namely the increase in student enrollment. The regression analysis shows that 90.4% of the variation in the increase in student enrollment can be explained by the people (human resources) and technology variables, while the remaining 9.6% is explained by other factors not examined in this study.